Village Policing--Early Modern Systems of Order in the Countryside - Wüst, Wolfgang (Advances in Social Sciences Research Journal, 2022)
The collection of sources on “good” policey has, so far, illustrated and interpreted the characteristics of early modern regulatory policy with territorial or urban examples. This was examined for a period which, as the saddle period of modernity, was responsible for setting a course that can hardly be overestimated, according to which rights and duties, public and ecclesiastical order, social peace, honour, happiness, health and prosperity are partly derived to this day. This temporal framework remained in this essay, but the social perspective changed. While many publications on ordinances were tailored to the role of the nobility and the courts, the municipal councillors, the imperial ecclesiastical chancelleries or the executive offices in the Reichskreise (Imperial Circles), the focus is now on their social reflections. The perspective from “below” becomes more effective. The rural area, village cooperatives, agrarian forms of trade and action remote from capitals and centres are the new, undoubtedly no less interesting focus.